Evaluation of Patients with Liver Biopsy According to the Liver Imaging-Reporting and Data System - Koç, Ali; Kayalı, Alperen (Cerrahpaşa Medical Journal, 2024)
Objective: The aim of the study is to evaluate patients with liver biopsy and histopathological diagnosis according to the Liver Imaging Reporting and Data System (LI-RADS) reporting system and to determine the degree of consistency of the LI-RADS system with histopathological data. Methods: The histopathological results of a liver biopsy and dynamic imaging were present in 123 cases, which were evaluated according to the LI-RADS radiological reporting system. Major features of LI-RADS and the success of LI-RADS in excluding and predicting hepatocellular cancer (HCC) and non-hepatocellular cancer were evaluated. Results: The major features of the LI-RADS and Arterial phase hyperenhancement (APHE) were 94.7%, wash-out 84.2%, capsule 89.2%, and threshold growth of 31.6% in HCC. The histopathology of all patients included in the LR-M category also showed non-HCC malignancy. All patients evaluated in the LR-5 group were diagnosed with HCC, except for 1 patient. In that 1 patient who was not diagnosed with HCC, a biopsy may not have been taken from the appropriate area due to the presence of multiple lesions. The histopathological differential diagnosis range of the patients in the LR-3 and LR-4 groups was found to be quite wide. Conclusion: The abnormal imaging area was characterized in accordance with LI-RADS; its consistency and sensitivity to histopathological data were found to be quite high. Training, dissemination, and implementation of the LI-RADS will increase the consistency and sensitivity of this reporting system. According to our study, we suggest that due to the wide differential diagnosis presence in the LR-3 and LR-4 classes, these cases should be evaluated more carefully, and a multidisciplinary approach would be extremely beneficial. Cite this article as: Koç A, Kayalı A. Evaluation of patients with liver biopsy according to the liver imaging-reporting and data system. Cerrahpaşa Med J. 2024;48(1):67-73.